The Effectiveness of Creative Problem Solving-Flipped Classroom for Enhancing Students' Creative Thinking Skills of Online Physics Educational Learning - Rahayu, S.; Setyosari, P.; Hidayat, A.; Kuswandi, D. (Jurnal Pendidikan IPA Indonesia, 2022)
Physics science differs from other educational programs. As a natural science subject, this study program has many mathematical formulas, complex scientific laws, theorems, and scientific postulates. This study program needs creative thinking skills since physics learning is related to creativity in solving scientific problems. CPS (Creative Problem Solving) and flipped classrooms are some efforts to increase creative thinking skills. In Indonesia, COVID-19 is the main reason for conducting online learning. However, there is no supporting information about the effectiveness of CPS and flipped classrooms as methods for online physics learning in university. Thus, this study aims to identify the effectiveness of CPS–flipped classrooms assisted by videos in enhancing university students' creative thinking skills for online learning. The study participants were university students from the Physics Education Study Program (population = 66 students, random cluster sampling for the sampling method) of Mataram University. They were divided into the control and experimental or treatment groups. This study used a pre-test and post-test group design (seven description questions). All questions were validated and reliable. All data were analyzed using an N-gain score and t-test. The results show that the N-gain score is in the medium zone. The data were normally and homogeneously distributed. The analysis result using the t-test shows that the addition of flipped classrooms is more effective than the control group (CPS only). CPS-flipped classroom performs better than CPS, proving the ability of flipped classrooms as the alternative method in online learning.